Influence of milling on the adsorption ability of eggshell waste. (March 2016) - Baláž, Matej; Ficeriová, Jana; Briančin, Jaroslav
Abstract: Eggshell waste was successfully used for the removal of heavy metal ions from model solutions. The effect of ball milling on the structure and adsorption ability of eggshell (ES) and its membrane (ESM) was investigated, with the conclusion that milling is benefitial only for the ES. The adsorption experiments showed that the ESM is a selective adsorbent, as the adsorption ability toward different ions decreased in the following order: Ag(I) > Cd(II) > Zn(II). The obtained Q m values for Ag(I) adsorption on the ESM and ES were 52.9 and 55.7 mg g −1, respectively. The potential industrial application of ES was also demonstrated by successful removal of Ag(I) from the technological waste. Graphical abstract: Highlights: Eggshell waste is an effective adsorbent of heavy metals. The selectivity of the ESM toward different ions was confirmed. The effect of milling on the adsorption ability is different for ES and ESM. Two-fold morphology of the milled ES was observed. ES is suitable for the adsorption of Ag(I) from the industrial waste.